Standardization of CD62P measurement: results of an international comparative study. Issue 1 (6th February 2013) - Levin, E.; Serrano, K.; Devine, D. V.
<x xml:space="preserve">Abstract</x> Background and Objectives Despite long being a mainstay in describing platelet activation via degranulation, interlaboratory variation remains an issue in measurement of membrane CD62P by flow cytometry. Our objective was to identify actions that may minimize this variation. Materials and Methods Sixteen laboratories participated in an international comparative study. Two sets of platelet samples were prepared in one laboratory. Set 1 was stained and fixed; set 2 was fixed and required staining at participating laboratories. A single‐staining method was used, and platelet populations were selected based on forward scatter/side scatter characteristics. Calibration beads were used to standardize measurement across different instruments. Results There was a large discrepancy in reported CD62P values among study sites [interlaboratory coefficient of variance (CV): 36–78%]. When electronic data were re‐analysed by a single analyst using a consistent gating strategy and a stable reference point, variation decreased markedly (CV < 12%), indicating a problem with isotype control samples, possibly related to sample fixation or shipment. Conclusion Consensus regarding gating strategies and use of a reliable reference point would greatly improve agreement in interlaboratory CD62P measurement.